Violation of Maxims in Garfield's Utterances in Garfield Comic Strips - Grace Sonia Simarmata; Umar Mono; Ely Hayati Nasution (Universitas Muhammadiyah Lampung, 2021)
ABSTRACTThis research examines violation of maxims of Garfield in Garfield comic strips. The purpose of this research is to find out types of maxims that are violated, describe how maxims are violated, and find out the reason behind the violation in Garfield’s utterances in Garfield comic strips. This research is descriptive qualitative. This research uses Cooperative Principle and Violation Maxim theories by Herbert Paul Grice. The data collection method used is documentation and note-taking. The data analysis method used is interactive model by Miles and Huberman with the cycle: data condensation, data display, and conclusion drawing/verifying. The results and discussion obtained is 15 comic strips that contain violation of maxims with 5 cases of violation of multiple maxims and 10 cases of violation of one single maxim and 11 reasons of violation of maxim (to save face, avoid of what is asked, cheer up hearer, convince hearer, deceive hearer, abuse verbally, avoid talking, satisfy hearer, hide the truth, express excitement, and get intension faster). Violation of maxim is dominated by violation of maxim of quantity with 9 cases in 9 comic strips. There are 8 cases of violation of maxim of quality in 8 comic strips, 2 cases of violation of maxim of manner in 2 comic strips, and 1 case of violation of maxim of relation in 1 comic strip.Keywords: Grice’s Violation Maxim, Utterance, Comic